Effeciency of Various Supportive Treatments as A Cure for Anaemia in Cattle with Theileriosis - Altug, Nuri; Yüksek, Nazmi; Keles, Ihsan; Özkan, Cumali; Yörük, Ibrahim Hakkı; Arslan, Sezai (The Thai Journal of Veterinary Medicine, 2014)
<span style="font-family: ’Book Antiqua’,’serif’; font-size: 9pt; mso-bidi-font-family: ’Angsana New’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH; mso-no-proof: yes;">The purpose of this study was to investigate the efficiency of various supportive treatments on the restoration of anaemia in theileriosis. A total of 20 cattle infected with theileriosis received intramuscularly a single dose of buparvaquone (2.5 mg/kg-1 bw) and were divided into 4 equal groups according to the different therapy options: whereas no supportive treatment was applied in group 1, administrations of vitamin B complex, antioxidant vitamins (A, D, E and C), minerals and trace elements were performed in groups 2, 3 and 4, respectively. Haematological parameters, serum concentrations of antioxidant vitamins, minerals and trace elements as well as serum glutathion peroxidase (GSH-Px) and superoxide dismutase (SOD) activities were determined before treatment and 7 days after in infected animals and compared to control values from 10 healthy cattle. In the theileriosis affected cattle, remarkable decreases in haematocrit values, haemoglobinaemia and platelet counts were associated to decreased serum α- / γ-tocopherol, vitamin C, vitamin B12, Ca, Mg, Zn, Na, GSH-Px and SOD levels and to increased sideraemia. The iron concentrations remained elevated and some antioxidants (α- / γ-tocopherol and vitamin C concentrations and GSH-Px and SOD activities) decreased in all treated cattle. Haematocrit values, haemoglobinaemia and vitamin B12 concentrations also remained depressed but maximal increases were recorded in cattle receiving vitamins B as supportive therapy (group 2). In parallel, platelet numeration was significantly restored in all groups, but specifically in group 2. On the other hand, the maximal increases in α-tocopherol and Zn concentrations recorded in groups 3 and 4, respectively, were not associated with cure of anaemia. These results show that the most efficient supportive therapy in the cure of anaemia during theileriosis was vitamin B administration.